2019
DOI: 10.5194/amt-12-2631-2019
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of primary standard mixtures for atmospheric oxygen measurements with less than 1 µmol mol−1 uncertainty for oxygen molar fractions

Abstract: Abstract. Precise monitoring of changes in atmospheric O2 levels was implemented by preparing primary standard mixtures with less than 1 µmol mol−1 standard uncertainty for O2 molar fractions. In this study, these mixtures were crafted in 10 L high-pressure aluminium alloy cylinders using a gravimetric method in which unknown uncertainty factors were theoretically determined and subsequently reduced. Molar fractions of the constituents (CO2, Ar, O2, and N2) in the primary standard mixtures were mainly resolved… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 58 publications
2
18
0
Order By: Relevance
“…The N 2 O-AOU for M99 was 0.088 ± 0.003 nmol µmol −1 , with an intercept of 1.6 ± 0.04 nmol and an R 2 of 0.69. This is a low value, nearly identical to results from the eastern basin of the subtropical North Atlantic, where South Atlantic Central Water is found (Cohen and Gordon, 1979;Suntharalingam and Sarmiento, 2000;Walter et al, 2006), and the eastern equatorial Atlantic (Arévalo-Martínez et al, 2017). Frame et al (2014) showed that most of the N 2 O in the Benguela Current region is produced in the water column and in the sediment by nitrifier denitrification (Frame et al, 2014).…”
Section: Stoichiometrysupporting
confidence: 81%
See 1 more Smart Citation
“…The N 2 O-AOU for M99 was 0.088 ± 0.003 nmol µmol −1 , with an intercept of 1.6 ± 0.04 nmol and an R 2 of 0.69. This is a low value, nearly identical to results from the eastern basin of the subtropical North Atlantic, where South Atlantic Central Water is found (Cohen and Gordon, 1979;Suntharalingam and Sarmiento, 2000;Walter et al, 2006), and the eastern equatorial Atlantic (Arévalo-Martínez et al, 2017). Frame et al (2014) showed that most of the N 2 O in the Benguela Current region is produced in the water column and in the sediment by nitrifier denitrification (Frame et al, 2014).…”
Section: Stoichiometrysupporting
confidence: 81%
“…In the case of O 2 , the atmospheric concentration was measured only sporadically with flask samples, so it was taken as a static value, viz. the mole fraction of O 2 in standard dry air, 0.2093 (Aoki et al, 2019). The in situ aqueous solubility of O 2 was calculated using the equations of García and Gordon (1992), of N 2 O using those in Weiss and Price (1980), and of CO 2 using Weiss (1974).…”
Section: Shipboard Air-sea Flux Density Estimatesmentioning
confidence: 99%
“…Although the highest CO 2 concentration of the gravimetrically prepared standard of the NIES-09 scale is similar to that of the TU-10 scale, a slope of 0.974 ppm ppm −1 is derived from a least-squares regression line fitted to the relationship between the CO 2 concentrations observed by NDIR on the TU-10 scale and those by CRDS on the NIES-09 scale with a correlation coefficient (r) of 0.978. On the other hand, we obtained a slope of 1.002 per meg per S. Ishidoya et al: O 2 : CO 2 exchange ratio for net turbulent flux meg −1 (r = 0.999) from the regression line fitted to the relationship between the O 2 concentrations of gravimetrically prepared standard gases (Aoki et al, 2019) measured by the mass spectrometer on the AIST scale and the gravimetric values of the standard gases covering a much wider range than the atmospheric variations in the O 2 concentration. Therefore, the uncertainty in OR due to the span uncertainties of O 2 and CO 2 concentrations is expected to be within 3 %.…”
Section: Continuous Measurements Of the Atmospheric Omentioning
confidence: 72%
“…The CH 4 , N 2 O and CO 2 concentrations are determined against Tohoku University (TU) scales, which are based on gravimetrically prepared primary standard gases (Aoki et al, 1992;Tanaka et al, 1983). Uncertainties of the TU primary standards are < ± 0.2, 0.2 and 0.03 % for CH 4 , N 2 O and CO 2 concentrations, respectively (Aoki et al, 1992 . Example of a calibration procedure for greenhouse gas concentration.…”
Section: Standard Gasesmentioning
confidence: 99%